Notes to Specify the Sociological Analysis of Generations - Montali, Guido (2025)
Abstract: This article aims to conduct a critical review of the concept of generations from a sociological perspective to elucidate its analytical potential. To this end, firstly, the subject is introduced, and the ambiguities inherent in the concept, particularly regarding its temporal and spatial extension, are identified. Secondly, an exploration is proposed into the various interpretations of its use, starting with the studies of Karl Mannheim and subsequently delving into contemporary receptions utilizing theoretical tools derived from Pierre Bourdieu. From this exploration, the utility of understanding generations within specific social spaces is derived. Hence, thirdly, its intersection with notions of field (from Bourdieu himself) and traditions (from Raymond Williams) is addressed, gauging its application in the peculiarities of the political field and narratives within traditions. Finally, the article concludes with a synthetic review of the problematic points highlighted in the introduction and with the main contributions of the proposal.